The complete mitochondrial genome of the Megalobrama pellegrini (Teleostei: Cyprinidae). (2nd September 2016) - Liu, Xueqing; Xiao, Kan; Zhao, Xun; Liu, Juanjuan; Zhang, Xu; Guo, Wentao; Chen, Lei; Du, Hejun
Abstract: The complete mitochondrial genome of Megalobrama pellegrini was determined by using a PCR-based sequencing method. The mitochondrial was 16, 620 bp in length, including 13 protein genes, two ribosomal RNA ( r RNA) genes, 22 transfer RNA ( t RNA) genes, and one control region. All genes were encoded on the heavy strain except for ND6 and eight t RNA genes. The gene arrangement of M. pellegrini was similar to those found in the other Megalobrama species. Base composition of the heavy strain was A (31.19%), T (24.69%), C (46.37%), G (16.22%) and with A + T bias of 55.88%.